Comparison of Quality of Life, Dysfunctional Attitudes and Defense Mechanisms in Patients with Chronic Back Pain with Healthy Individuals - shabannejad Chenani *, Elham (Shahroud Journal of Medical Sciences, 2025)
Background: Chronic pain is the leading cause of human suffering and disability worldwide, significantly impacting the quality of life for individuals. This study aimed to compare the quality of life, dysfunctional attitudes, and defense mechanisms between patients suffering from chronic back pain and individuals who are in good health. Methods: The type of study conducted is descriptive causal-comparative research. Fifty male and female patients seeking treatment at the Rasht Pain Clinic were included in the study, chosen through purposive sampling. The control group, consisting of fifty individuals with no history of chronic back pain, was selected using convenience sampling in May 2021. The Quality-of-Life Questionnaire (WHOQOL-BREF), Dysfunctional Attitude Scale (DAS), and Defense Style Questionnaire (DSQ-40) were given to both healthy individuals and patients. An analysis of the data was conducted through multivariate analysis of variance (MANOVA) using SPSS 23 software. Results: A multivariate analysis of variance in the current study revealed a significant difference between the two groups of patients and healthy individuals in terms of quality of life (physical, mental, relationships, environment), Dysfunctional Attitudes (perfectionism, need for approval, need to please others), and defense mechanisms (mature, neurotic, immature) (P-value<0.01, F11,88=16.63). However, there was no significant difference in the vulnerability component of dysfunctional attitude between the two groups of patients and healthy subjects. Conclusions: Identifying factors such as poor quality of life, maladaptive attitudes, and improper use of defense mechanisms can worsen chronic pain in individuals. Understanding the influences of these variables is crucial for enhancing the overall physical and mental well-being of patients experiencing chronic pain.